2002
DOI: 10.1080/08880010290097314
|View full text |Cite
|
Sign up to set email alerts
|

SPLENIC FUNCTION IN OMANI CHILDREN WITH SICKLE CELL DISEASE: Correlation with Severity Index, Hemoglobin Phenotype, Iron Status, and α -Thalassemia Trait

Abstract: The prevalence of functional asplenia in Omani children with sickle cell disease (SCD) has not been previously defined. In this study, the authors aim to compare the natural history of splenic dysfunction in their patients to other reports. The splenic function was studied in 72 Omani patients with sickle cell disease (50 homozygous for hemoglobin S (HbS-S), 11 double heterozygotes for HbS and beta(0)-thalassemia (HbS-beta(0)-thal), 5 HbS-beta(+)-thal, 5 patients with hemoglobin S-D disease, and 1 child with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 13 publications
4
20
0
Order By: Relevance
“…This is probably due to the reduction in the hemolytic rate (7,10,42), irreversibly sickled cells (6,14), as well as a possible decrease in inflammatory process. Also in concurrence with other studies, the mean levels of MCV (6)(7)(8)10,12,13,15,16,23,34,38,41,43,44) and MCH (6,8,15,23,43,44) were significantly lower in subjects with α-thal. This is due to the reduction in the synthesis of α chains (45).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is probably due to the reduction in the hemolytic rate (7,10,42), irreversibly sickled cells (6,14), as well as a possible decrease in inflammatory process. Also in concurrence with other studies, the mean levels of MCV (6)(7)(8)10,12,13,15,16,23,34,38,41,43,44) and MCH (6,8,15,23,43,44) were significantly lower in subjects with α-thal. This is due to the reduction in the synthesis of α chains (45).…”
Section: Discussionsupporting
confidence: 92%
“…Coexistence of α-thal apparently increases Hb A 2 levels in sickle cell anemia (8,13,15) and does not influence Hb F levels (9,15,16). Studies have shown that α-thal is associated with a reduced prevalence of cerebral stroke (6,20) and leg ulcers (6,21) and preserves splenic function (22,23), perhaps because of a reduction in hemolysis and improved PCV levels prejudicial effects are seen in complications that are perhaps more dependent on blood viscosity, such as painful episodes (15,16,18,24) and osteonecrosis (24,25). It has also been suggested that the coexistence of α-thal would prolong the life expectancy of patients with sickle cell anemia (26,27).…”
Section: Introductionmentioning
confidence: 96%
“…It is possible that the low number of SCJO cases may be due to the prevalence of preserved splenic function in Omani patients. 15 In the largest published case series to date, Olaitan et al reported that jaw osteomyelitis occurred predominantly in men (81%) among 16 SCJO patients. 6 Other reports have also noted a higher prevalence of SCJO among men.…”
Section: Discussionmentioning
confidence: 99%
“…Reports from the Eastern Province of Saudi Arabia and gulf region showed that spleen function is usually preserved in patients with sickle cell anemia (SCA) who presented with levels of Hb F higher than 20% and had a high prevalence of alpha thalassemia trait. Ngo et al, 2013;Wali et al, 2002) This study was conducted to see the abnormal splenic finding among patients with sickle cell disease in Al-Ahsa, aregion in the Eastern Province of Saudi Arabia. The study documented different splenic pathologies that were found among 119 patients.…”
Section: Extra-splenic Findings:-mentioning
confidence: 99%